Tranparansi dan Akuntabilitas Pengelolaan Dana Desa dalam Pencapaian Good Governance: Studi Kasus Desa Cepogo, Kabupaten Boyolali - Puji Astuti; Rochmi Widayanti; Ratna Damayanti (Universitas Proklamasi 45 Yogyakarta, 2021)
A village fund program is a form of government concern for the development of rural areas. The management of village funds consists of five stages, namely planning, implementation, managing, reporting, and responsibility, which should be based on the principles of good governance. The Cepogo Village Government, Cepogo District, Boyolali Regency, in Central Java Province is one of the village governments in Indonesia that has implemented the principles of good governance in managing village funds. This study aims to see how the implementation of the principles of transparency and accountability in the management of village funds by the Cepogo Village Government to achieve good governance standards. This study uses a descriptive qualitative approach. The data collection technique used was direct interviews with a semi-structured method. The participants of this study were the Village Head of Administration, Village Secretary, Village Treasurer, and staff of the Administration Section for managing the village fund who are responsible for managing it. The results showed that the planning and implementation of Village Fund Program activities had shown accountable and transparent management. In terms of accountability, both physical and management activities, it has shown that the implementation is accountable and transparent.